2003
DOI: 10.3151/jact.1.269
|View full text |Cite
|
Sign up to set email alerts
|

Tensile and Anti-Spalling Properties of Direct Sprayed ECC

Abstract: The use of Engineered Cementitious Composite (ECC), which has metal-like deformation and crack opening restriction ability, as a retrofit material for structures, has been the subject of high expectations. For this application, the direct spray method has been commonly accepted. This study focused on experimentally clarifying the fundamental properties of direct sprayed ECC containing high-performance polyvinyl alcohol fibers. The experiments that were performed demonstrated that direct sprayed ECC was success… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 12 publications
0
19
0
Order By: Relevance
“…As aforementioned, tensile ductility is the most important material property of SHCC, yet relatively large variation of tensile ductility was observed in the literature (Kanda et al 2002(Kanda et al , 2006Wang and Li 2004). To address such concern, Wang and Li (2004) have proposed using artificial flaws with prescribed size distribution as defect site initiator to create more saturated multiple cracks, resulting in more consistent tensile strain capacity among different specimens from the same batch.…”
Section: Introductionmentioning
confidence: 99%
“…As aforementioned, tensile ductility is the most important material property of SHCC, yet relatively large variation of tensile ductility was observed in the literature (Kanda et al 2002(Kanda et al , 2006Wang and Li 2004). To address such concern, Wang and Li (2004) have proposed using artificial flaws with prescribed size distribution as defect site initiator to create more saturated multiple cracks, resulting in more consistent tensile strain capacity among different specimens from the same batch.…”
Section: Introductionmentioning
confidence: 99%
“…ECC production has been poorly documented except for a few reports on a full-scale mixing test 4) . This study aims to obtain knowledge on quality assurance in full-scale production by a trial production in pre-cast concrete plants on a large scale.…”
Section: Experiments 21 Objectives and Test Parametersmentioning
confidence: 99%
“…The mix proportions used in this study are shown in Table 3., where Mix-N is based on the literature 4) and the Mix-M is nearly the same as Mix-N except for the substitution of OPC with MPC. These two mixes showed self-compacting fresh properties in laboratory mixing 3) , and slump flow values of over 500mm.…”
Section: Proportionsmentioning
confidence: 99%
See 2 more Smart Citations